Physical-Chemical Characterization and Mineralogic Analysis of Hydrothermal Systems Located in the Coconuco and the San Juan Sectors in Cauca, Colombia. (12th May 2019) - Torres-Ceron, Darwin Augusto; Acosta-Medina, Carlos Daniel; Restrepo-Parra, Elisabeth
Abstract : Hot springs of the volcanic zones are characterized for having high sulfur content in the form of sulphate and other ions resulting from chemical reactions. Sources with these types of elements are of great interest for the tourism and geothermal industry because of their highlighted properties which include therapeutic treatments, relaxation baths, agricultural applications, and preservation of flora and fauna among others. For these reasons, research oriented to carry out the characterization of these factors is of great importance to determine the availability of places with such characteristics. This work shows the characterization of 17 hot spring sources located in the Coconuco and San Juan sectors (Cauca, Colombia, South America). Water samples were taken in May 2017, and laboratory analyses were carried out by the Water Laboratory at Universidad Nacional de Colombia-Manizales, based on the Standard Methods (APHA-AWWA-WEF). Rock samples were taken in November 2017, and laboratory analyses were carried out by the GMAS + Laboratory (Bogotá, Colombia). The Piper, Stiff, and ternary (Giggenbach) diagrams were used for the classification of major ions. Mineralogy composition was determined through XRD and XRF. Results indicate that most sources are of the sulphated type according to the anions and of the calcium type according to the cations. In concordance with Giggenbach diagrams, most of the sources are immature waters and, despite their interaction with rocks, they have not achieved the equilibrium. Likewise, these sources are of heated vapor type and, considering that they consist of sulphated acid sources, it is not possible to evaluate the reservoir temperatures from Na/K cations. The low Ca 2+ /Mg 2+ ratio in the sources indicates the lack of direct migration of fluids and the high content of Ca 2+ and Mg 2+ regarding Na + and K +, which suggests that fluids possibly are mixed with cold waters rich in Ca 2+ and Mg 2+ . From the mineralogic characterization, it was observed that volcanic rocks are composed of cristobalite and albite with TiO2, Fe2 O3, and CaO traces and mineral sulfur. Metals like Cr, considered in this case as contaminants, are found in low concentrations in rocks and are not detected in these waters.